A study on the preparation of superhydrophobic Silane-MXene modified melamine foam and its oil-water separation performance - Wang, Wei; Song, Xiangning; Xie, Yan; Sheng, Xuejia; Zhang, Shucai (Frontiers in Materials, 2023)
In recent years, oil spills and organic pollution have caused severe damage to the ecological environment. Therefore, the treatment of oily wastewater has become a serious challenge. Here, with the help of melamine foams as a substrate, MXene nano-rough structures were built, and cetyltrimethoxysilane was grafted onto their surfaces to create an oil-absorbing material that is both user-friendly and effective at oil-water separation. Due to the nano structures of MXene were constructed and the long-chain silanes were modified on the foam surface, the material became superhydrophobic. In addition to being able to selectively absorb oils from an oil/water mixture (including emulsified oils) up to 111 times its weight, the modified foam was found to have a water contact angle of 157°which could selectively absorb oil but not water. Furthermore, it demonstrated sustained hydrophobicity and lipophilicity after experiencing strong acid/alkali or prolonged hightemperature treatment, allowing for various scenarios where oil-water separation can be used in severe settings without compromising performance.